Climate change in the news : a study of the british press - Carvalho, Anabela (2000)
The paper builds on an extensive study of the coverage of climate change by the British press from the mid-eighties until 1997. A corpus of over 2 000 articles published in the Guardian, Times and Independent is the basis for both a quantitative and qualitative analysis on the representation of this complex matter. Climate change is a contested issue at the scientific, political, economic and social levels. The media are a central arena for such a debate. As a marketplace of arguments, the media promote some ideas and voices while suppressing others. It is then urgent to identify potential structural biases, as well as challenges to the dominant positions. The mass means of communication have an important role in the social production, reproduction and change of views and values. In other words, the media matter for the discursive construction of a normative order about the global environment. The aims of the paper will be to provide an overview of the coverage of climate change by the British press and to critically examine some aspects of the representation of the issue. The paper will be structured in two parts. Firstly, I will present the fluctuation in the number of articles published in the press throughout a period of almost 15 years and discuss possible explanations of peaks and lows, as well as their impact. In the second part, I will investigate the ways the media represents the claims and views of different social actors - policy-makers, NGOs, business, scientists, etc. A sample of press articles will be analysed in detail to assess this point. Such an analysis will shed light on the political role of the media and help us know the extent to which the media tend to legitimate certain ideological positions or to promote a valuable critique of various alternatives. Another goal of the paper will be to examine the representation of ethical viewpoints in the press. Some of the themes to be explored are equity, justice and responsibility. The latter can be considered in relation to peoples geographically or culturally distant and in relation to future generations.